2017
DOI: 10.1016/j.neuropsychologia.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala functional connectivity is associated with locus of control in the context of cognitive aging

Abstract: Locus of control (LOC) measures the extent to which individuals perceive control over their lives. Those with a more “internal” LOC feel self-sufficient and able to determine important aspects of their own future, while those with a more “external” LOC feel that their lives are governed by events beyond their control. Reduced internal LOC and increased external LOC have been found in cognitive disorders, but the neural substrates of these control perceptions are yet unknown. In the present study, we explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 80 publications
(81 reference statements)
0
9
2
Order By: Relevance
“…The MPFC-amygdala connectivity may therefore reflect an anatomical substrate that synthesizes information from multiple resources – value of the self, emotional responses to experience related the controllability, and cognitive appraisal of controllability. Interestingly, the relationships between the amygdala-frontal functional connectivity and external LOC were different from those observed in our prior study that combined aMCI patients with cognitively healthy older adults ( Ren et al, 2017 ). For external LOC, the correlation was positive with the functional connectivity of ventral frontal region (MPFC)-amygdala in the current study, while the correlation was negative with the functional connectivity of the dorsal frontal regions (middle cingulate cortex and superior frontal gyrus)-amygdala in our previous study.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…The MPFC-amygdala connectivity may therefore reflect an anatomical substrate that synthesizes information from multiple resources – value of the self, emotional responses to experience related the controllability, and cognitive appraisal of controllability. Interestingly, the relationships between the amygdala-frontal functional connectivity and external LOC were different from those observed in our prior study that combined aMCI patients with cognitively healthy older adults ( Ren et al, 2017 ). For external LOC, the correlation was positive with the functional connectivity of ventral frontal region (MPFC)-amygdala in the current study, while the correlation was negative with the functional connectivity of the dorsal frontal regions (middle cingulate cortex and superior frontal gyrus)-amygdala in our previous study.…”
Section: Discussioncontrasting
confidence: 96%
“…These divergent findings may be due to different sample characteristics (i.e., using a cognitively diverse sample in our previous study compared to studying aMCI alone in the current study), but both of them may shed light on the altered LOC in the neurodegenerative process. Of note, we did not find any neural correlates of internal LOC in the current study; in our previous study, however, we found a positive relationship between internal LOC and anterior cingulate cortex/middle frontal gyrus ( Ren et al, 2017 ). It may be due to the difference in the sample characteristics as well.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations